Simulating the Characteristics and Influences of the Botswana High over Southern Africa using the Model for Prediction Across Scales (MPAS) - Maoyi, Molulaqhooa Linda (Department of Environmental and Geographical Science, 2023)
The Botswana High is a prominent mid-tropospheric system that modulates rainfall over subtropical Southern Africa, but the capability of a Global Climate Model (GCM) to reproduce the characteristics and influences of this system on drought remains unknown. Furthermore, the summer variability of the Botswana High has been linked to the El Niño Southern Oscillation (ENSO). However, it remains unknown whether the high's variability is a direct response to ENSO. To that end, this thesis examines the capability of a GCM with quasiuniform resolution (Model Prediction Across Scales, hereafter MPAS) in simulating the characteristics and influences of the Botswana High on drought modes over the subcontinent as well as the influence of ENSO on the high. To simulate the characteristics of the Botswana High and its influence on drought modes, the MPAS model is applied to simulate the global climate at 240km quasi-uniform resolution over the globe for the study period 1980-2010. The model results are validated against gridded observation dataset (Climate Research Unit, CRU), satellite dataset (Global Precipitation Climatology Project, GPCP), and reanalysis datasets (Climate Forecast System Reanalysis, CFSR; the National Oceanic and Atmospheric Administration, NOAA; and ERA-Interim reanalysis 5, ERA5). To investigate the response of the Botswana High to ENSO, this thesis carried out two MPAS model experiments. The first model experiment used observed SSTs everywhere during the study period, while the second experiment used observed SSTs everywhere except over the Pacific Ocean, where monthly climatological SSTs are imposed. The results of this thesis show that MPAS replicates all the essential features in the climatology of climate variables (e.g. temperature, rainfall, 500 hPa geopotential height and vertical motion) over Southern Africa, reproduces the spatial and temporal variation of the Botswana High, and captures the influence of the Botswana High on droughts and deep convections over the subcontinent. In all the datasets (CRU, ERA5, 20C and MPAS), the most dominant five Drought Modes (hereafter DM1-DM5) over Southern Africa jointly explain more than 60% of the interannual variability in the 3-month summer droughts for SPEI and for SPI. ERA5 and MPAS agree that the Botswana High influences the interannual variability of DM1; however, the influence is strong in ERA5 (r = -0.85) and moderate in MPAS (r = -0.42). In addition to that, wet years (+ve SPEI and SPI) are characterized by a weak Botswana High and drought years (-ve SPEI and SPI) by a strong Botswana High. In addition to that, the wet and dry years correspond to the -ve and +ve phases of El Niño Southern Oscillation (ENSO), respectively. Given this, the results of this thesis suggest that the Botswana High might be a conduit pipe through which ENSO signals influence DM1 over the region. Investigation into the impact of ENSO on the Botswana High reveals that the absence of ENSO forcing reduces the amplitude of the Botswana High variability, but the signal of the variability remains. While ENSO enhances the strength of the Botswana High, it does not aid the formation of the High. The result of the thesis has application in the improvement and application of MPAS for drought early warning systems over Southern Africa.